2019
DOI: 10.4195/nse2018.09.0016
|View full text |Cite
|
Sign up to set email alerts
|

Values Use in Undergraduate Students’ Socio‐Hydrological Reasoning: A Comparative Study

Abstract: Core Ideas Socio‐scientific issues prepare students for real‐world experiences. Socio‐hydrological reasoning involves the use of values. Value identifications differ between developing and developed countries. Value use frequency differs between developed and developing countries. Growing human populations place increasing demands on our planet, resulting in an array of challenges with both scientific and non‐scientific dimensions. These challenges are collectively known as socio‐scientific issues (SSIs). It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Although the demand for research that illuminates the potential for undergraduate courses that do so is high, few studies have explored the development of SSR in the context of SHI. In doing so, this study builds upon and contributes to prior research on teaching and learning about natural and managed water systems, particularly in undergraduate STEM [11][12][13]19,20,52,53] and non-STEM [54,55] contexts, where new courses that employ innovative, effective approaches to exploring challenges regarding water resource use and management are emerging (e.g., [2,12,13,19,48,[56][57][58][59]. Additionally, the findings herein contribute to the broader literature base focused on SSI teaching and learning, where SSI have served as viable contexts for the development of science content knowledge and practice skills (e.g., [31,32], as well as habits of mind and reasoning skills, such as perspective taking and exhibiting skepticism when confronted with various media [39], that are not scientific in nature, but equally important to the development of informed resolutions [17,48,[60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the demand for research that illuminates the potential for undergraduate courses that do so is high, few studies have explored the development of SSR in the context of SHI. In doing so, this study builds upon and contributes to prior research on teaching and learning about natural and managed water systems, particularly in undergraduate STEM [11][12][13]19,20,52,53] and non-STEM [54,55] contexts, where new courses that employ innovative, effective approaches to exploring challenges regarding water resource use and management are emerging (e.g., [2,12,13,19,48,[56][57][58][59]. Additionally, the findings herein contribute to the broader literature base focused on SSI teaching and learning, where SSI have served as viable contexts for the development of science content knowledge and practice skills (e.g., [31,32], as well as habits of mind and reasoning skills, such as perspective taking and exhibiting skepticism when confronted with various media [39], that are not scientific in nature, but equally important to the development of informed resolutions [17,48,[60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Given that SSI have generally served as meaningful contexts for students' to better understand the science concepts that underlie SSI, as well as for reasoning about societal aspects of SSI by way of engagement in SSR (i.e., functional scientific literacy), we would expect SHI to serve similarly as meaningful contexts for the development of functional water literacy. Studies have begun to emerge that illustrate some of the criteria students consider when making decisions about the resolution of SHI [19], systems thinking they employ [42], and how their personal values inform their reasoning [20]. However, the potential for the SSR construct to provide a concrete means for developing functional water literacy in the context of SHI is underexplored, particularly in undergraduate courses with a direct focus on water.…”
Section: Ssr About Shimentioning
confidence: 99%
“…Students emphasized components more strongly in their diagrammatic models than mechanisms or phenomenon/patterns (Figure 2). When students reason about an SHS, their values and experiences inform their ideas and decisions [5]. Student experiences with water frame, particularly their firsthand experiences, may have directly contributed to the emphasis of components in diagrammatic models.…”
Section: Discussionmentioning
confidence: 99%
“…Sociohydrologic systems (SHS), are water systems that include both human and natural dimensions. However, research has shown students are challenged by reasoning about both natural and human dimensions of SHS (e.g., [4][5][6][7][8][9]). To support students' systems thinking about SHS, we developed and implemented a new interdisciplinary undergraduate course.…”
mentioning
confidence: 99%
“…This framework, more so than the other three, is highly contextualized. Examples of work done in this area include studies on student reasoning on real-world systems like coastal eutrophication (Sell et al, 2006;McNeal et al, 2008), ecosystem dynamics (Grotzer et al, 2013;Sutter et al, 2018), soil microbial activity (Appel et al, 2014), and socio-hydrologic systems (Gunckel et al, 2012;Sabel et al, 2017;Forbes et al, 2018;Petitt and Forbes, 2019).…”
Section: Authentic Complex Earth and Environmental Systemsmentioning
confidence: 99%